Correlations and coexistence of characteristics describing body posture and feet in children and young people of both sexes aged 7 to 13 years - Mirosław Mrozkowiak; Karol Bibrowicz; Tomasz Szurmik; Roland Hadlich (Kazimierz Wielki University, 2017)
Introduction. Few publications have addressed the static-dynamic correlations of characteristics concerning the regions of feet and pelvic girdle. The problem was explored by Mięsowicz. Development of IT solutions allows for a more comprehensive approach to evaluation of body posture and examination of temporal and spatial relationships between individual components and evaluation of spatial balance in the vertical body posture. The aim of this study was to determine the significance of the correlation between selected characteristics that describe the system of the pelvis, spine and feet in the population of children of both sexes aged 7 to 13. Material and methods. The examinations conducted in a group of children and young people aged 7 to 13 years allowed for recording 12,898 observations, including 6,938 girls and 5,960 boys, and values of 121 characteristics that describe body posture and feet across individual age and sex categories. The test stand for evaluation of body posture and feet using the photogrammetric method is composed of a personal computer, software, screen and printer, and projection-reception device with a camera for measurement of selected parameters. Conclusions 1.   The most frequent and strongest correlations and their coexistence with the characteristics in the area of feet occur in the groups of girls aged 11 and 12 years and boys aged 11, 12 and 13 years.   2.   No regularities and logical relationships were found between the parameters of the pelvis-spine-feet system in any age range and any sex. • Among the characteristics which describe the pelvis-spine system and are most often correlated with feet characteristics are the characteristics of the sagittal and frontal planes, followed by less pronounced characteristics of the transverse plane.       Furthermore, among the characteristics of the feet which are most often correlated with the parameters of the pelvis and spine system are the characteristics that describe  valgus and varus deformities of the fifth toe and varus deformity of the hallux of the right foot.